Acute Toxicity of Chenopodium ambrosioides and Annonamuricata oils with Acaricidal Potentials - Adinci, Kossi Justin; SESSOU, PHILIPPE; DOUGNON, T. VICTORIEN; Assogba, Fidèle; TOWANOU, RODRIGUE; KOMAGBE, GWLADYS; DOUGNON, TOSSOU JACQUES; LALEYE, OLABISSI ANATOLE A.; FAROUGOU, SOUAÏBOU (My University, 2019)
Background and Objective: Recently, the acaricidal activities of the essential oil extracted from the leaves of Chenopodium ambrosioides L. (EOCA) and the almonds oil of Annona muricata (OAMA) have been proven in vitro on the invasive tick Rhipicephalus microplus in Benin. For a better valorization of these products as substitutes of synthetic acaricidal molecules which have shown their limits, it is recommended to determine the safety of these oils. The purpose of this study was to evaluate the acute oral toxicity of these extracts. Material and Methods: To this end, test was performed according to the OECD Test Guidelines 425 at a single dose of 2000 mg kg–1 body weight/oral route of each oil. Selected biochemical and hematological parameters were determined at 0, 7 and 14 days. Then, the organ toxicity of the oils was evaluated by histopathological examination at the end of the assay. Results: There were no deaths or significant alterations in live weight in the OAMA group. Administration of OAMA caused an increase in transaminase levels (ASAT and ALAT) and urea and a decrease in creatinine. Histopathology showed that there were no alterations in the kidney but some liver disturbances were observed. With respect to EOCA, all rats in the group treated with this extract died at a single dose of 2000 mg kg–1 body weight. Histopathology revealed some renal and hepatic changes. Conclusion: The single oral dose of OAMA and EOCA induces toxic alterations in Wistar rats suggesting the cautious use of these phytoacaricides externally as animals may tend to lick the products.
Keywords: Chenopodium ambrosioides; Annona muricata; anti-tick; Rhipicephalus microplus; toxic substances; histopathology